Menggali Makna Anugerah Dalam Kematian Yesus Kristus dan Implikasinya Bagi Jemaat Masa Kini - Posumah, Kanaya Fiorensia Christina; Wanget, Samuel Wailan Leonard; Kawuwung, Jefry (Proskuneo: Journal of Theology, 2024)
This paper explores the doctrine of salvation, or Soteriology, with a particular focus on the significance of God's grace in the redemptive work of Jesus Christ. The doctrine of salvation continues to generate considerable questions among congregations. Numerous complex questions arise concerning the means by which human beings are saved, leading to debates within religious communities. The aim of this research is to address these questions raised by congregations regarding the work of salvation, the grace bestowed upon humanity, and the meaning of Jesus' death on the cross. The researcher examines various theories within systematic theology, particularly Soteriology, as a framework for this study. A qualitative approach with a descriptive analysis method was employed, as this research seeks to uncover the diverse meanings and understandings held by congregants regarding the concept of grace in God's redemptive work. The findings reveal that: (1) the salvation experienced or obtained by human beings is an expression of God's love for humanity. (2) Congregants' understanding of Jesus' death is characterized by the manifestation of the fruits of the Spirit as guiding principles in their daily lives. The compassion shown by God attests to the inherent value of human life in God's sight.